The computation of electromagnetic fields at non-asymptotic distances from an antenna using cylindrical near-field measurements - Du Toit, Cornelis Frederik (Stellenbosch : Stellenbosch University, 2012)
Dissertation (Ph. D.) -- University of Stellenbosch, 1992.